Identification of Risk Factor of Adolescent Sexual Behavior in Purwokerto: Pilot Study - Endang Triyanto (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Introduction: Adolescent students drop out of school due to sexual behavior. They are depressed and pregnant. The level and risk factors of sexual behavior in Purwokerto are not comprehensively known. Aim: The purpose of this study was to determine the level and risk factors of sexual behavior. Methods: This study uses a quantitative method approach. This type of research is a survey. A survey using the questionnaire that has been statistically tested. Respondents were selected by simple random sampling from April to August 2022 in Purwokerto-Indonesia. Researchers have conducted screening to select adolescents who have risky sexual behavior. A number of 41 adolescents are included in high risk. The data analysis used was descriptive statistics. The data are presented in a frequency distribution table.  Result: These risk factors come from individuals, peers, family, and the environment. Risk factors that have been found in this study include lack of knowledge (17%), dating behavior (66%), the negative influence of peers (78%), disharmonious family (32%), lack of attention from parents (56%), a victim of divorce (7%), free environment (68%), the negative influence of social media (61%), and negative values and beliefs (54%). The highest risk factor is peers (78%). Conclusion: All risk factors significantly affect adolescent sexual behavior. Peers was the factor which most highly influence sexual behavior. Therefore, adolescents should have assertive abilities so they are not easily influenced.